Primary cutaneous cryptococcal infection due to fingolimod – Induced lymphopenia with literature review. (2020) - Patil, Sachin M.; Beck, Phillip Paul; Arora, Niraj; Acevedo, Bran Andres; Dandachi, Dima
Abstract: Cryptococcus. Neoformans (C. neoformans) is an encapsulated heterobasidiomycetous fungus responsible for opportunistic infections worldwide in immunocompromised patients. Clinical presentation ranges from asymptomatic respiratory tract colonization to disseminated infection in any human body part. The central nervous system (CNS) and pulmonary diseases garner most of the clinical attention. Secondary cutaneous cryptococcosis is an uncommon manifestation seen as a sentinel sign commonly in disseminated cryptococcal infection. Primary cutaneous cryptococcosis (PCC) is a rare manifestation seen in both immunocompromised and immunocompetent patients. It is a discrete infection with different epidemiological trends. Immunosuppressive therapy (corticosteroids, tacrolimus) predisposes a patient to acquire this clinical entity. We present a case of an elderly Caucasian male on fingolimod for relapsing-remitting multiple sclerosis with nonhealing scalp lesions for four years. He was a referral to our healthcare center for the presence of fungal elements seen on a scalp biopsy fungal stains. Final cultures returned positive for C. neoformans susceptible to fluconazole (MIC = 8 μg/mL). The CD4 count was 13 cells/uL, and workup for CNS and disseminated cryptococcal infection were negative. Fingolimod is an immunomodulator that acts on sphingosine 1-phosphate receptors, affecting the lymphocytes. Pubmed literature review revealed few case reports (< 5) with PCC in patients on fingolimod. To our knowledge, ours is the first case with scalp cryptococcosis, with the lowest CD4 count while being on fingolimod. No randomized controlled trial data exist for the treatment of PCC. Therapy initiated with oral luconazole for six months with significant improvement at three months.